Dietary Prevention of Colitis by Aronia Berry is Mediated Through Increased Th17 and Treg. Issue 5 (13th December 2018) - Pei, Ruisong; Martin, Derek A.; Valdez, Jonathan C.; Liu, Jiyuan; Kerby, Robert L.; Rey, Federico E.; Smyth, Joan A.; Liu, Zhenhua; Bolling, Bradley W.
Abstract : Scope: Increased fruit consumption is associated with reduced risk of colitis. It has been investigated whether the anti‐colitic effects of the polyphenol‐rich aronia berry ( Aronia mitschurinii 'Viking') are mediated through Th17 and Treg. Methods and results: Colitis is induced in recombinase activating gene‐1 deficient mice injected with syngeneic CD4 + CD62L + naïve T cells. Mice consume either 4.5% w/w aronia‐berry‐supplemented or a control diet concurrent with T cell transfer. The extent of colitis and immunocyte populations are evaluated at weeks 3 to 7 after transfer. Aronia consumption prevents colitic wasting and reduces colon weight/length ratios relative to the control diet at weeks 5 and 7. Compared to the control diet, aronia feeding increases Treg in mesenteric lymph node at all colitis stages. Treg and regulatory Th17 subpopulations (IL‐17A + IL‐10 + and IL‐17A + IL‐22 + ) are increased in lamina propria and spleen at week 5 in aronia‐fed mice. Aronia feeding also decreases total CD4 + cells but increases colonic Tregs. The ability of aronia to modulate colonic cytokines is associated with functional T cell IL‐10 and increased diversity of microbiota. Conclusions: Aronia berry consumption inhibits adoptive transfer colitis by increasing Treg and regulatory Th17 cells. Dietary modulation of T cells is dynamic and precedes colitic wasting. Abstract : T cell transfer to mice lacking B and T cells induces colitis, which is inhibited by aronia berry consumption. Aronia berry consumption improves colon health and inhibits colitis‐associated body weight loss. The anti‐colitic effects of aronia berry are partly attributed to increased anti‐inflammatory Th17, Treg, and improved gut bacterial composition. Functional IL‐10 is necessary for dietary modulation of Treg and colonic cytokines, but aronia inhibits colitis independently of these mechanisms.